2015
DOI: 10.1037/emo0000051
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive trait anxiety, situational stress, and mental effort predict shifting efficiency: Implications for attentional control theory.

Abstract: Attentional control theory (ACT) predicts that trait anxiety and situational stress interact to impair performance on tasks that involve attentional shifting. The theory suggests that anxious individuals recruit additional effort to prevent shortfalls in performance effectiveness (accuracy), with deficits becoming evident in processing efficiency (the relationship between accuracy and time taken to perform the task). These assumptions, however, have not been systematically tested. The relationship between cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 32 publications
6
70
1
2
Order By: Relevance
“…For example, although models of anxiety have suggested that an important consequence of chronic rumination and worry should be manifest as worse working memory (Eysenck & Derakshan, 2011; Pessoa, 2009), as well as loss of inhibitory control over time due to ego depletion (Granic, 2014), empirically, broad evidence of such impairments have been difficult to consistently document (Berggren & Derakshan, 2013). Ongoing work in the area suggests that chronic rumination and worry may simultaneously increase motivation to perform well, thus cancelling out any performance deficits that might otherwise have been observed (Braver et al, 2014; Edwards, Edwards, & Lyvers, 2015; Pessoa, 2009). Similarly, substantial heterogeneity in neurocognitive performance is also found in depression (McClintock, Husain, Greer, & Cullum, 2010), with evidence that executive dysfunction is not observed among depressed patients who demonstrate valid effort during testing (Benitez, Horner, & Bachman, 2011; Rohling, Green, Allen, & Iverson, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For example, although models of anxiety have suggested that an important consequence of chronic rumination and worry should be manifest as worse working memory (Eysenck & Derakshan, 2011; Pessoa, 2009), as well as loss of inhibitory control over time due to ego depletion (Granic, 2014), empirically, broad evidence of such impairments have been difficult to consistently document (Berggren & Derakshan, 2013). Ongoing work in the area suggests that chronic rumination and worry may simultaneously increase motivation to perform well, thus cancelling out any performance deficits that might otherwise have been observed (Braver et al, 2014; Edwards, Edwards, & Lyvers, 2015; Pessoa, 2009). Similarly, substantial heterogeneity in neurocognitive performance is also found in depression (McClintock, Husain, Greer, & Cullum, 2010), with evidence that executive dysfunction is not observed among depressed patients who demonstrate valid effort during testing (Benitez, Horner, & Bachman, 2011; Rohling, Green, Allen, & Iverson, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have already explored interactions between state and trait anxiety on shorter (i.e., within-experiment) timescales (212, 213) and computational accounts of the effects observed in these studies, or related effects, could also be developed. Reductions in attentional control due to stress, for example, could interact with over-general fear conditioning to severely disrupt concentration (the former effect increasing distractibility; the latter increasing the number of distractions).…”
Section: Outstanding Computational Questionsmentioning
confidence: 99%
“…Two studies have showed that individuals with higher levels of trait anxiety perform worse on measure of performance effectiveness, including total errors (Casselli, Reiman, Hentz, Osborne, & Alexander, 2004), perseverative errors (Caselli, et al, 2004), or the failure to maintain sets (Gershuny & Sher, 1995). More recently, another study (Edwards, Edwards, & Lyvers, 2015) examined performance on the WCST using a measure of processing efficiency (based on the reaction time [RT] on perseverative errors). Although their results suggested that the association between trait anxiety and WCST efficiency may be specific to certain situations (i.e., when mental effort was high, or when mental effort was low but levels of situational stress were high), performance was impaired in trait anxiety across most task conditions (the only situation that did not show an association with anxiety was when both mental effort and situational stress were low).…”
Section: Trait Anxiety and Task-set Shifting: Prior Research And A Nementioning
confidence: 99%
“…Similarly, we will also not discuss here two recent studies that examined the relationship between trait anxiety and shifting using a dual-task paradigm (Edwards, Moore, Champion, & Edwards, 2015; Johnson & Gronlund, 2009), because there is some evidence that dual-tasking ability might be separable from shifting ability (e.g., Alzahabi & Becker, 2013; Miyake et al, 2000). …”
mentioning
confidence: 99%